Objective assessment of handwriting in outpatient prescriptions of a tertiary care hospital - Mohan, Prafull; Gupta, Pooja (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Poor physician handwriting may lead to wrong comprehension and dispensing errors. This study was planned to objectively assess the quality of handwriting of doctors and their readability by physician, pharmacist and patient and to explore the impact of experience and familiarity of pharmacist on prescription readability. Methods: A 100 prescriptions were selected and were given to a pharmacist, a doctor and an educated lay person. They rated the readability of prescriptions on a scale of 1-10 and an average readability score was calculated. Prescriptions with average score 4 or less were subjected to analysis by a pharmacist working at the hospital dispensary (P1) and another pharmacist not working at hospital pharmacy (P2). Results: Average score of pharmacist, physician and lay person was 6.14, 5.2 and 3.14 respectively. A total of 28 prescriptions, containing 93 medicines, had an average readability score of 4 or less. P1 was not able to comprehend one medicine while P2 could not comprehend 19 medicines out of these 93. The performance of both pharmacists was compared by diagnostic tests (EPI 6.04D). The sensitivity of P2 was 80% (95% CI 70.6-87.7), specificity and positive predictive value were 100, and negative predictive value was 5.3 (0.3-28.1). Conclusions: Familiarity of the pharmacist with the prescribing physicians’ handwriting is an important factor in comprehension of poorly legible prescriptions. This could limit the patients to pharmacists around the prescribers. Implementation of appropriate steps need to be assured to minimize the prescription errors.